2021
DOI: 10.3389/fimmu.2021.712936
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Temporal Proteome Profiling Reveals the Immunological Triple Offensive Induced by Synthetic Anti-Cancer Salmonella

Abstract: The engineered “obligate” anaerobic Salmonella typhimurium strain YB1 shows a prominent ability to repress tumor growth and metastasis, which has great potential as a novel cancer immunotherapy. However, the antitumor mechanism of YB1 remains unelucidated. To resolve the proteome dynamics induced by the engineered bacteria, we applied tumor temporal proteome profiling on murine bladder tumors after intravenous injection of either YB1 or PBS as a negative control. Our data suggests that during the two weeks tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…PC‐3 prostate cancer, [ 12 , 110 ] breast tumor, [ 109 , 111 ] HCC, [ 112 ] colon carcinomas, [ 109 , 111 , 112 , 113 ] CT26 colon cancer, [ 114 ] MC38 colon cancer, [ 115 ] schwannoma, [ 116 ] bladder cancer, [ 92 , 117 ] PDAC, [ 12 , 118 ] fibrosarcoma [ 119 ]…”
Section: Bacteria As a Double‐edge Sword In Cancermentioning
confidence: 99%
“…PC‐3 prostate cancer, [ 12 , 110 ] breast tumor, [ 109 , 111 ] HCC, [ 112 ] colon carcinomas, [ 109 , 111 , 112 , 113 ] CT26 colon cancer, [ 114 ] MC38 colon cancer, [ 115 ] schwannoma, [ 116 ] bladder cancer, [ 92 , 117 ] PDAC, [ 12 , 118 ] fibrosarcoma [ 119 ]…”
Section: Bacteria As a Double‐edge Sword In Cancermentioning
confidence: 99%
“…It is widely reported that STm induces a cascade of immune changes within the tumour microenvironment—such as widespread immune cell influx, pro-inflammatory cytokine production, dendritic cell (DC) maturation and natural killer (NK) cell activation—that is believed to support immune tumour-clearance (Yang et al, 2021). Indeed, monocyte depletion (Johnson et al, 2021), NK cell depletion (Lin et al, 2021), or MyD88 deletion (Zheng et al, 2017) can wholly abrogate therapeutic success in vivo , underscoring the necessity of an innate-like response in this therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some bacteria-based biohybrid systems show potential in synergistic cancer therapy. Anaerobic or facultative anaerobic characteristics enable bacteria to possess hypoxia tropism for active tumor targeting. , In addition, the immunogenicity of bacteria facilitates it with immune activity. ,, Propionibacterium acnes (PA), as an anaerobic bacterium with oxygen tolerance, is a commensal organism in human skin . The hypoxic TME is preferential for PA to proliferate and metabolize.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In addition, the immunogenicity of bacteria facilitates it with immune activity. 13,15,16 Propionibacterium acnes (PA), as an anaerobic bacterium with oxygen tolerance, is a commensal organism in human skin. 17 The hypoxic TME is preferential for PA to proliferate and metabolize.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation